Empresas integradoras y desarrollo local en Michoacán: una propuesta metodológica - González Mejía, Erika Jenny (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The analysis of the opposing results, he leads us to reflecting about the relevancy of a methodology that grants to the local development consistency and objectivity with a multidisciplinary vision. It makes the above mentioned us question if the local development has already been constituted like body epistemológico concluding that there is no consensus with regard to the concept of the same one, which makes the approach of a methodology difficult. Also one concludes that there are ambiguous concepts inside the local development like that of actor and company. The constructive criticism of these concepts there will be points of developing in future investigations for the purpose of contributing to the evaluation of social processes of integral development.

El análisis de los resultados encontrados, nos lleva a reflexionar acerca de la pertinencia de una metodología que otorgue al desarrollo local consistencia y objetividad con una visión multidisciplinaria. Esto último nos hace cuestionar si el desarrollo local se ha constituido ya como cuerpo epistemológico concluyendo que no hay consenso respecto al concepto del mismo, lo cual dificulta la aproximación de una metodología. También se concluye que hay conceptos ambiguos dentro del desarrollo local como el de actor y empresa. La crítica constructiva a estos conceptos serán puntos a desarrollar en futuras investigaciones con la finalidad de contribuir a la evaluación de procesos sociales de desarrollo integral.
Facultad de Economía Vasco de Quiroga. Maestría en Ciencias en Desarrollo Local
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2009-0003; Empresa integrada; Pertinencia; Procesos sociales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4963